Quadratic Inequality for Obtaining Fixed Point Using Property (E.A) in Menger Spaces - Jyotsana Majumdar; Koti N.V.V. Vara Prasad (IndoMS, 2022)
In this paper, we establish some common fixed point theorems for two pairs of self-mappings by using the notion of occasionally weakly compatible/common property (E.A) using an inequality involving quadratic terms in Menger PM-space and these results are partially extend the some known results in the literature.